Heterogeneous Beliefs and Momentum Profits - Verardo, Michela (Journal of Financial and Quantitative Analysis, 2009)
Abstract Recent theoretical models derive return continuation in a setting where investors have heterogeneous beliefs or receive heterogeneous information. This paper tests the link between heterogeneity of beliefs and return continuation in the cross-section of U.S. stock returns. Heterogeneity of beliefs about a firm’s fundamentals is measured by the dispersion in analyst forecasts of earnings. The results show that momentum profits are significantly larger for portfolios characterized by higher heterogeneity of beliefs. Predictive cross-sectional regressions show that heterogeneity of beliefs has a positive effect on return continuation after controlling for a stock’s visibility, the speed of information diffusion, uncertainty about fundamentals, information precision, and volatility. The results in this paper are robust to the potential presence of short-sale constraints and are not explained by arbitrage risk.